NRF2, a member of the NFE2 family of transcription factors, is not essential for murine erythropoiesis, growth, and development - Chan, Kaimin (The National Academy of Sciences of the USA, 1996)
The locus control region of the β-globin gene is composed of four erythroid-specific hypersensitive sites. Hypersensitive site 2 has been shown to be a powerful enhancer and contains a tandem repeat sequence for the transcription factors AP1 and NFE2 (activating protein 1 and nuclear factor erythroid 2, respectively). The human NRF2 (NFE2 related factor 2) has been isolated by bacterial expression screening using this core sequence as a probe. p45-NFE2, NRF1, and NRF2 belong to the CNC (“cap ‘n’ collar”) subfamily of the basic region–leucine zipper transcription factors, which exhibits strong homology at specific regions such as the “CNC” and the DNA binding and leucine zipper domains. Although the erythroid-specific p45-NFE2 has been implicated in globin gene regulation, p45-NFE2 null mice succumb to bleedings due to lack of platelets and those that survive exhibit only a mild anemia. To determine the function of NRF2, which we found to be widely expressed in vivo, we have characterized the genomic structure of the mouse NRF2 gene, disrupted the Nrf2 gene by homologous recombination in mouse embryonic stem cells (ES cells), and generated NRF2(−/−) mice. Homozygous mutant mice developed normally, were not anemic, reached adulthood, and reproduced. Our studies indicate that NRF2 is dispensable for mouse development.